Case Report: Ultrasound Sciatic and Saphenous Nerve Blocks for Tibial Malunion Surgical Correction in a Pediatric African Leopard (Panthera pardus) - Ravasio, Giuliano; Brioschi, Federica Alessandra; Rabbogliatti, Vanessa; Gioeni, Daniela; Di Cesare, Federica; Corletto, Federico; Oltolina, Maurizio; Carnevale, Liliana (Frontiers in Veterinary Science, 2020)
Little information is available regarding ultrasound guided locoregional anesthesia in non-domestic species. Locoregional techniques have been shown to reduce intra-operative anesthetic requirements and provide postoperative pain relief. Decreasing dosage of general anesthetics allows more stable cardiopulmonary function during anesthesia and reduces the probability of side effects. A 11-week-old African leopard (Panthera pardus) was referred for treatment of a malunion angular limb deformity secondary to a tibial and fibular fracture. The animal was scheduled to undergo angular correction of the tibia via closing wedge osteotomy and fixation with a locking plate system. Following preanesthetic medication and induction of general anesthesia, a saphenous nerve block (ropivacaine 0.5%; 0.15 mL/kg) was performed under ultrasound guidance and a sciatic nerve block (ropivacaine 0.5%; 0.15 mL/kg) was performed using ultrasound and a peripheral nerve stimulator. Intraoperative anesthetic plane was considered light, yet no abrupt cardiocirculatory changes were seen, nor rescue analgesia required. This case report suggests that sciatic and saphenous blockade could therefore be recommended as part of a multimodal plan of analgesia for orthopedic surgeries in pediatric exotic felids